An Exploration of Child–Staff Interactions That Promote Physical Activity in Pre-School - Kippe, Karin Oddbjørg; Fossdal, Tom Stian; Lagestad, Pål Arild (Frontiers in Public Health, 2021)
A previous study identified a significant association between the average physical activity levels of pre-school staff and children during pre-school hours but did not determine if this association was initiated by pre-school staff or children. The present study aimed to explore the interactions between children and staff to better understand the conditions of such a relationship. Observations using the Environment and Policy Assessment and Observation (EPAO) protocol were carried out in three pre-schools, and a focus-group interview and semiformal interviews were conducted with five pre-school staff in one of the three pre-schools to examine the research question. Both the observations and the interview data revealed that physical activity by pre-school staff initiated physical activity among the children. The findings pointing to the importance of pre-school staff as organizers of the physical activity of children and the willingness of staff to join a physical activity initiated by the children also appear to be important. The findings also indicate that most of the physical activity took place outdoors. The study highlights the importance of pre-school staff as major contributors to the physical activity of pre-school children.